Economias de escala no sistema financeiro brasileiro no período pós-estabilização - Lima Neto, Antonio Francisco de (2017)
This work aims to analyze economies of scale in the Brazilian Financial System after the introduction of Plano Real (2001 – 2009), which led to a significant expansion of local bank portfolio. To do so, this paper compares results obtained from a minimum cost function, with Transcendental Logarithmic (TRANSLOG) specification, and administrators’ preferred cost function, which maximizes management utility, derived with the aid of Almost Ideal Demand System (AIDS). The results show economies of scale for the chosen set of Financial Conglomerates when the AIDS technique is applied in contrast to the diseconomies of scale evidenced with the aid of TRANSLOG technique. The results come in line with the findings of international research, pointing out the benefits of application of the AIDS technique in the field of banking efficiency, given the multiplicity of objectives bank administrators must currently pursue.